Creativity, Collaboration and Motivation of a High School Teacher - Dronova, Svetlana Yurievna; Shiganova , Yulia Mikhaylovna; Ozarnov , Ruslan Vladislavovich; Micallef, Larisa Olegovna; Brega, Alexandr Vasilievich (Journal of Ecohumanism, 2024)
The article discusses the role of motivation in the teacher’s professional activity, the influence of creativity and autonomy on a teacher’s motivation level in the choice of teaching methods, forms and instruments, as well as the students themselves and the educational organization’s direction. The author analyzes the possibilities of realizing the teachers’ creative potential in their professional activities, regardless of the subjects taught, to increase the motivation of both the teachers themselves and students. Techniques are proposed for effective cooperation between the administration and the teaching staff.